(untitled) (BIOM - Revue scientifique pour la biodiversité du Massif central, 2022)
The first mention of Tettigettalna argentata in the Allier department is reported. A synthesis of the knowledge of the cicadas of the Allier is drawn up. Currently, three species are considered as part of the cicadofauna of this department.